Some Information on Topographic Features and the Characteristics of the Ice Sheet around the Yamato Mountains - Yoshida, Yoshio; Mae, Shinji (1978)
P(論文) Some information and suggestions for future field and theoretical works for meteorite search and glaciology in the Yamato Mountains region, Antarctica are presented based on the preliminary mapping of surface features of the ice sheet by interpretation of aerial photographs and compilation of previous works. A considerably large extent of bare ice areas may be concerned with both regional and local topographies of the ice sheet. Several minor features are distinguished, mapped and described in connection with the movement of ice. The slope of marginal part of the ice sheet at its maximum stage is inferred from glacial topographies of the Yamato Mountains and coastal ice-free areas and from the continental shelf. The results are not conclusive but to be tested by future works. This, in its turn, may be useful as a kind of framework for future field works. departmental bulletin paper